Membranes In Organic Micropollutants Removal - Bodzek, Michal; Konieczny, Krystyna (Current Organic Chemistry, 2018)
The occurrence of micro-pollutants in natural waters (surface and groundwater) as well as in wastewaters, has become a worldwide issue of a great importance for environmental protection strategies. First of all, disinfection by-products, endocrine disrupting, pharmaceuticals and personal care products are taken into account. The paper gives a brief outline on recent advances in the detection and removal of this pollutants in/from water and wastewater. Conventional and advanced treatment technologies capable of removing these trace organic compounds, with a specific focus on membrane technology, i.e. reverse osmosis and nanofiltration, microfiltration and, ultrafiltration, as well as membrane bioreactors and forward osmosis have been described. Reverse osmosis and nanofiltration can remove nearly all discussed compounds to the levels below permissible limits, but some hydrophobic and small organic trace contaminants may not be effectively rejected by nanofiltration membranes. Double systems, such as reverse osmosis/advanced oxidation processes or double pass reverse osmosis and membrane bioreactor/reverse osmosis are found to be the most suitable in the removal of micro-pollutants. Microfiltration and ultrafiltration, while considered to organic micropollutants removal, has to be integrated with coagulation, adsorption, chemical complexion or biological reactors. A specific emphasis on the emerging forward osmosis process, which can potentially be a major platform for the next generation water and wastewater treatment technologies, has been made.
Keywords: Organic micropollutants